Formation of nanoclusters in the transition of carbon dioxide to the supercritical state - Borts, B.V.; Skoromnaya, S.F.; Tkachenko, I.V.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2022)
Supercritical fluid extraction (SFE) with CO₂ is widely used to extract biological materials, metal complexes and their isotopes. Supercritical CO₂ (SC-CO₂) is an environmentally friendly, efficient, and affordable solvent. However, the change in the chemical and physical properties of CO₂ in the transition to the supercritical (SC) state has not been studied so far. The paper proposes to consider such a change as a result of the formation of elementary linear, flat or volumetric nanoclusters, from which large nanoclusters can also be formed. Based on the theory of repulsion of valence electron pairs, the geometry of the arrangement of atoms in elementary nanoclusters is described. The change in the chemical and physical properties of CO₂ is confirmed by absorption spectra in the IR range for wavelengths of 4.2…4.4 μm in sub- and SC-CO₂. Надкритична флюїдна екстракція СО₂ широко використовується для вилучення біологічних матеріалів, комплексів металів та їх ізотопів. Надкритичний СО₂ є екологічно чистим, ефективним та доступним розчинником. Однак до цього часу не досліджено зміну хіміко-фізичних властивостей СО₂ при переході до надкритичного стану. У роботі запропоновано розглядати таку зміну як результат формування елементарних лінійних, плоских або об’ємних нанокластерів, з яких можуть формуватися нанокластери великих розмірів. На основі теорії відштовхування валентних електронних пар описано геометрію розташування атомів у елементарних нанокластерах. Зміна хіміко-фізичних властивостей СО₂ підтверджується за допомогою спектрів поглинання в ІЧ-діапазоні для довжин хвиль 4,2…4,4 мкм у до- та надкритичному СО₂.